1991
DOI: 10.1113/jphysiol.1991.sp018693
|View full text |Cite
|
Sign up to set email alerts
|

The influence of induced hypocapnia and sleep on the endogenous respiratory rhythm in humans.

Abstract: SUMMARY1. Ventilation has been studied during hypocapnia produced by passive mechanical ventilation in ten normal human subjects.2. During wakefulness, disconnection of the ventilator led to inconsistent apnoea of only brief duration. During sleep, at a similar degree of hypocapnia, disconnection of the ventilator led more consistently to apnoea which was also of much longer duration; the deeper the sleep stage, the longer the apnoea.3. The resumption of breathing during sleep could precede or follow arousal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
57
2

Year Published

1994
1994
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 20 publications
4
57
2
Order By: Relevance
“…In humans, apnoeas or unstable breathing patterns can be induced by small reductions in Pa,CO 2 below the resting level both in sleep [29,30] and sometimes in the awake state [26,[31][32][33]. Venous carbon dioxide unloading by haemodialysis [16,27] and the ventilatory response to transient carbon dioxide pulses during recovery from voluntary overbreathing [34] suggested that the apnoeic threshold for Pa,CO 2 may be up to 1.3 kPa below the resting level, but with wide individual variation.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, apnoeas or unstable breathing patterns can be induced by small reductions in Pa,CO 2 below the resting level both in sleep [29,30] and sometimes in the awake state [26,[31][32][33]. Venous carbon dioxide unloading by haemodialysis [16,27] and the ventilatory response to transient carbon dioxide pulses during recovery from voluntary overbreathing [34] suggested that the apnoeic threshold for Pa,CO 2 may be up to 1.3 kPa below the resting level, but with wide individual variation.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent in general with ours in demonstrating an apnoeic threshold well below the resting level of PET,Co2 This threshold can be decreased by hypoxia (Honda, Natsui, Hasumura & Nakamura, 1963;Lahiri et al 1978) and by after-discharge, which also tends to prevent periodic breathing, whereas anaesthesia, sleep, altitude and metabolic alkalosis favour instability and periodicity (Cherniack, Euler, Homma & Kao, 1979). Passive HV in hyperoxia in non-rapid eye movement (REM) sleep in subjects who did not show awake post-hyperventilation apnoea resulted in apnoea when PCo2 fell 3-6 mmHg below the sleeping rest value and 1-2 mmHg below the awake rest value, with increase in incidence of apnoea both with increasing depth of sleep and in hyperoxia (Datta et al 1991). Similar results were obtained in hypoxia (Skatrud & Dempsey, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Moser et al (1965) showed more apnoea in hyperoxia, but normal breathing following both active and passive HV has also been described (Ashbridge, Jennett & North, 1972;Jennett, Ashbridge & North, 1974;Skatrud & Dempsey, 1983;Datta et al 1991), as has hyperpnoea, at least in the minute or so following the end of HV (Mills, 1946;Fink, 1961;Tawadrous & Eldridge, 1974;Swanson, Ward & Bellville, 1976;Folgering & Durlinger, 1983;Cummin, Sidhu, Telford & Saunders, 1992). Most of these studies were performed in normoxia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The picture is completely different during sleep or under anaesthesia. Several studies have shown that, under these circumstances, the maintenance of respiratory rhythm is critically dependent on chemical feedback [41,[48][49][50]. Reducing Pa,CO 2 by only a few mmHg causes apnoea.…”
Section: Chemical Feedbackmentioning
confidence: 99%